2023
DOI: 10.1177/08919887231202948
|View full text |Cite
|
Sign up to set email alerts
|

Antidementia Medication Use in Nursing Home Residents

Brian R. Ott,
Carl Hollins,
Jennifer Tjia
et al.

Abstract: Background Antidementia medication can provide symptomatic improvements in patients with Alzheimer’s disease, but there is a lack of consensus guidance on when to start and stop treatment in the nursing home setting. Methods We describe utilization patterns of cholinesterase inhibitors (ChEI) and memantine for 3,50,197 newly admitted NH residents with dementia between 2011 and 2018. Results Overall, pre-admission use of antidementia medications declined from 2011 to 2018 (ChEIs: 44.5% to 36.9%; memantine: 27.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…13 A national study of newly admitted NH residents from 2011 to 2018 reported a lower odds of initiating ChEIs and memantine after admission and a higher odds of discontinuing antidementia medications among those who were using antipsychotics before admission. 14 In that study, initiation and/or discontinuation of antidementia medications after admission were also associated with dementia severity and other factors including age, Medicaid enrollment, recent hospitalizations, comorbid mental health conditions, and polypharmacy. 14 Other studies have focused only on antidementia medication use.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…13 A national study of newly admitted NH residents from 2011 to 2018 reported a lower odds of initiating ChEIs and memantine after admission and a higher odds of discontinuing antidementia medications among those who were using antipsychotics before admission. 14 In that study, initiation and/or discontinuation of antidementia medications after admission were also associated with dementia severity and other factors including age, Medicaid enrollment, recent hospitalizations, comorbid mental health conditions, and polypharmacy. 14 Other studies have focused only on antidementia medication use.…”
mentioning
confidence: 87%
“…14 In that study, initiation and/or discontinuation of antidementia medications after admission were also associated with dementia severity and other factors including age, Medicaid enrollment, recent hospitalizations, comorbid mental health conditions, and polypharmacy. 14 Other studies have focused only on antidementia medication use. An analysis of the 2004 National NH Survey indicated that approximately 30% of NH residents with dementia were being treated with ChEIs.…”
mentioning
confidence: 87%
See 2 more Smart Citations